2006
DOI: 10.5194/acp-6-349-2006
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variation patterns of total ozone and lower stratospheric temperature in observations and model simulations

Abstract: Abstract.We report results from a multiple linear regres-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
29
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 57 publications
9
29
0
Order By: Relevance
“…Linear regressions showed that the mean amplitude of the QBO signal is about 2-4% of the mean column ozone (WMO, 1999). The ENSO is also known to influence column ozone (Shiotani et al, 1992;Randel et al, 1994;Steinbrecht et al, 2006). However, unlike the QBO, the effects of ENSO on column ozone are mostly visible in the zonal distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Linear regressions showed that the mean amplitude of the QBO signal is about 2-4% of the mean column ozone (WMO, 1999). The ENSO is also known to influence column ozone (Shiotani et al, 1992;Randel et al, 1994;Steinbrecht et al, 2006). However, unlike the QBO, the effects of ENSO on column ozone are mostly visible in the zonal distribution.…”
Section: Introductionmentioning
confidence: 99%
“…But some of these differences may again be due to deficiencies in the ERA-40 (Punge and Giorgetta, 2007). For an analysis of the temperature QBO in the nudged version of MAECHAM4-CHEM in comparison to observations we refer to Steinbrecht et al (2006). They evaluated a model experiment that is almost identical to the QBO experiment in this study, except for its duration of 40 years.…”
Section: Model and Comparison To Observationsmentioning
confidence: 99%
“…The modulation of the ozone column in our model was investigated by Steinbrecht et al (2006). In this article, the vertical distribution of ozone is of particular interest.…”
Section: Model and Comparison To Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the interannual variability in ozone can be explained by external forcings like the QBO and the solar cycle (e.g. Steinbrecht et al, 2006). The co-variability of the time series of the two simulations, as measured by the correlation coefficient, gives a measure of how deterministic the system is, i.e.…”
Section: Temperature and Ozonementioning
confidence: 99%